Developing sustainable, green and inclusive agricultural value chains in the Caribbean and the Pacific Islands - Westlake, M.J. (Technical Centre for Agricultural and Rural Cooperation, 2014)
Using evaluations of nine case studies in seven countries, this insightful book aims to draw comparisons between value chains in the Caribbean and the Pacific. Employing a useful summary of key findings, along with tables, maps and figures, the text reviews a wide range of factors affecting commercial value chain development in the two regions. Emphasis is placed on how the chains studied have maximised the inclusion of smallholders and on identifying ways in which they have been able to address sustainability concerns.